First record of the Kuwana pine mealybug Crisicoccus pini (Kuwana) in Italy: a new threat to Italian pine forests? - Boselli, Mauro; Pellizzari, Giuseppina (Zootaxa, 2016)
The Asiatic Kuwana pine mealybug, Crisicoccus pini (Kuwana, 1902) (Hemiptera, Pseudococcidae), is reported in Italy for the first time. It was detected in September 2015 on maritime pine, Pinus pinaster, and stone pine, Pinus pinea, trees growing in the town of Cervia (Ravenna Province), Northern Italy. The mealybug has caused yellowing and decline of the pine trees. Pinus pinea is recorded here as a new host for C. pini.